Climatic Observation Versus People Perception: A Case Study in the Ampesekrom Community Near Nkawkaw in the Kwahu West Municipal of Ghana. (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: This research examines community perspectives on climate change in Ampesekrom, near Nkawkaw, situated in Ghana's Eastern Region. The study employs a combined methodology that integrates meteorological data evaluation with community questionnaires (involving 100 participants) to explore trends in climate variability and adaptation strategies within forest-reliant communities. The meteorological evaluation identifies clear decade-by-decade temperature and precipitation trends across the three-decade timeframe. Peak temperatures show a general upward trajectory with significant variations, whereas precipitation patterns exhibit early decreases followed by more recent increases. A comparative evaluation with Abetifi, a neighbouring high-altitude station (positioned at 601m elevation compared to Nkawkaw's 275m), demonstrates varying climate effects associated with elevation and land use modifications. Precipitation patterns exhibited considerable variation, with significant decreases from the initial to the middle decade (roughly 15-25% reduction) before experiencing modest recovery during the final decade. Survey results indicated extensive recognition of climate change (98.5% confirmed that the climate is changing), accompanied by nuanced comprehension of the anthropogenic factors contributing to environmental transformation. Participants pinpointed forest clearing, farming intensification, vegetation burning, and urban development as key factors driving environmental transformation, revealing their understanding of connections between human actions and climatic conditions. The study recommends implementing community-focused educational programs that clarify climate change origins, indicators, and adaptation approaches through understandable terminology and contextually relevant illustrations. Additionally, it suggests enhancing agricultural advisory services that deliver technical guidance for climate adaptation, guaranteeing consistent interaction between agricultural advisors and farming communities, while improving climate information accessibility to support better agricultural planning and risk mitigation decisions.